Evaluation of Nutrition Habits of Adolescents in the Aspect of Gender and Physical Activity - Daiva Vizbaraitė; Rasa Jankauskienė; Aušra Griciūtė; Kristina Visagurskienė; Simona Pajaujienė (Lithuanian Sports University, 2018)
Research background and hypothesis. Nutrition habits develop with the growth of an individual. During adolescence proper nutrition habits and physical activity are the most important factors inﬂ uencing health. The quality of life is affected by the peculiarities of behavior and lifestyle in adolescence. The aim of our study was to determine nutrition habits of adolescents, and then, to make a comparison of eating patterns by gender and the groups of adolescents in different physical activity groups. Research methods. The study comprised the ninth form students from 16 Kaunas schools (4 gymnasiums, 10 secondary and 2 main schools). The strategy was based on the evaluation of proportions of the different types of schools in Kaunas. The study applied questionnaire survey. Research results. The analysis revealed that 28.5% of middle-school age students did not have breakfast, there were more girls than boys among them. Boys and students with lower physical activity more frequently had hot meals. Adolescents most commonly had meals four times per day without following nutrition regimen. Discussion and conclusions. Boys more frequently had breakfast, however, they chose buns, potato chips, and used more fried food for snacks; the same eating patterns were followed by students with lower physical activity. Girls were more likely to have fruit, green vegetables. In most cases, the selection of meals depended on the individual taste; boys more frequently paid attention to prices and nutrition values. Usually adolescents acquired information about proper nutrition from their parents and the internet; girls - more frequently from magazines and the internet. Keywords: adolescents' knowledge on healthy nutrition, nutrition habits, physical activity.